IVF-ICSI split insemination reveals those cases of unexplained infertility benefitting from ICSI even when the DNA Fragmentation index is reduced to 15% or even 5% - Mustafa, Kamarul Bahyah; Yovich, John L; Marjanovich, Nicole; Yovich, Steven J (Andrology & Gynecology: Current Research, 2016)
The aim of the study was to assess the fertilization rate (FR) of randomized sibling oocytes inseminated by conventional IVF or ICSI in couples with unexplained infertility. Methods The 16-month study was conducted at an established private IVF facility. Oocytes recovered from couples with normal semen parameters and normal DNA fragmentation index (DFI; <30%), were randomly allocated to IVF or ICSI and the FR (2PN/MII) was assessed. Pregnancy outcome following embryo transfers were analyzed with regards to either IVF-embryo vs. ICSI-embryo, and in relation to DFI levels. Results Of 585 oocytes retrieved from 38 patients, 463 were mature (MII). The ICSI group generated a significantly higher number of 2PN embryos with a mean FR of 83.4% vs. 67.6% (p<0.05). There were no cases of complete fertilization failure (CFF) in the ICSI group, but there were 7.9% in the IVF group. The significant difference of FR was observed only when the DFI level was ≥ 15% and if such cutoff was applied, the CFF cases would be reduced to 2.6%. Of the 30 patients who had fresh embryo transfers performed, the ICSI group showed a higher pregnancy rate (69.2% vs. 58.8%; N.S.) with a significantly higher mean DFI value in the non-pregnant group (p<0.05). Conclusions IVF-ICSI split insemination can reveal those cases which will benefit from ICSI even where semen parameters and DFI are normal; however if the DFI is reduced to a 15% cut-off level, the rate of CFF will be minimized, but not completely excluded, even at 5%..